Investigation of selected antibiotic residues in marine aquaculture wastewater / Thiang Ee Lean - Thiang , Ee Lean (2021)
The occurrence and distribution of sulfonamides, macrolides, tetracyclines, fluoroquinolones, trimethoprim, lincomycin, carbadox and four resistance genes in bacteria (tet(M), sul1, sul2 and sul3) in surface waters collected from seven main aquaculture production states in Peninsular Malaysia were investigated. Among the analytes, tetracyclines, sulfonamides and fluoroquinolones were detected at 83%, 72% and 69% frequency, respectively. Twenty-three antibiotics were present in aquaculture farms at the concentration ranging from LOQ to 957685.1 ng/L and revealed a wide distribution of antibiotics in Malaysian aquaculture farms. Moreover, the occurrence of antibiotic resistance genes in bacteria for tet(M), sul1 and sul2 were detected in more than 90% of the sites, indicating their ubiquitous occurrence in Malaysian aquaculture farm. According to the calculated Risk Quotient, ciprofloxacin, enrofloxacin norfloxacin and lincomycin exceeded the value of 1, and posed a high ecological risk to the relevant aquatic microorganism in Kelantan, Perak Pahang and Johor Further assessment is needed to monitor the antibiotic residues in aquaculture systems to mitigate environmental antibiotic resistance and potential transmission to humans through the food chain.